THE EFFECT OF TALKING CHIPS TECHNIQUE TOWARD THE STUDENTS SPEAKING SKILL AT SMAN 1 SALO - Fera Lisa; Lusi Marleni (Universitas Pahlawan Tuanku Tambusai, 2017)
This experimental research was conducted at the eleventh grade students of SMA Negeri 1 Salo. This research is aimed to gives the effect toward the students speaking skill by using talking chips technique. The sample of this research consists of two classes; class XI IPA2 was used as the experimental group treated by using Talking Chips technique and class XI IPA1 as the control group treated by using question and answer technique. Experimental class consists of 23 students and control class consists of 24 students. The sampling technique used is purposive sampling. The instruments used to collect the data are speaking test and documentation. The data were analyzed by using SPSS 20 program. Based on the result finding, the average score in experimental class was 72.69 and 57.33 in control class. Based on the data Analysis of Variance it can be seen that the class factor showed that Fo is 96.67 with significant (2-tailed) of 0.000 smaller than 0.05. It can be conclude there was the effect or talking chips technique toward the students speaking skill at the eleventh grade students of SMA Negeri 1 Salo.